(untitled) (Physical Education, Health and Social Sciences, 2025)
The growing urgency of climate change and environmental degradation has intensified pressure on small and medium-sized enterprises (SMEs) to adopt sustainable business practices. Green entrepreneurship and green innovation have emerged as critical mechanisms through which SMEs can contribute to sustainable development while maintaining competitiveness. However, the effectiveness of these green strategies largely depends on governance structures that guide decision-making, accountability, and stakeholder engagement. This study investigates the impact of green entrepreneurship and green innovation on the sustainable development of SMEs, with a particular focus on the mediating role of governance. Employing a mixed-method research design, the study integrates quantitative data collected from a survey of 200 SMEs engaged in green initiatives with qualitative insights obtained through semi-structured interviews with managers and key decision-makers. Structural Equation Modeling (SEM) is used to test the proposed hypotheses, while thematic analysis is applied to qualitative data to deepen understanding of governance dynamics. The findings are expected to demonstrate that green entrepreneurship and green innovation positively influence SMEs’ sustainable development outcomes and that governance significantly mediates and strengthens these relationships. Effective governance mechanisms—such as leadership commitment, transparent management practices, and supportive regulatory frameworks—enhance the successful adoption and implementation of green initiatives. This research contributes to the existing literature by empirically clarifying the governance–sustainability nexus in SMEs and offers practical implications for policymakers, SME managers, and stakeholders seeking to promote sustainable development in alignment with the United Nations Sustainable Development Goals (SDGs).